Primary Intracranial Adenoid Cystic Carcinoma: Report of Three Cases - Tsetsos, Nikolaos; Poutoglidis, Alexandros; Terzakis, Dimitrios; Epitropou, Ioannis; Oostra, Amanda; Georgalas, Christos (Journal of Neurological Surgery Part B: Skull Base, 2022)
Objective Nasal cavity and paranasal sinuses host a variety of malignant tumors with adenoid cystic carcinoma (ACC) being the most frequent cancer of salivary gland origin. The histological origin of such tumors virtually precludes primarily intracranial localization. The aim of this study is to report cases of primarily intracranial ACC without evidence of other primary lesions at the end of an exhaustive diagnostic workup.Methods An electronic medical record search complemented by manual searching was conducted to identify prospective and retrospective cases of intracranial ACCs treated in Endoscopic Skull Base Centre Athens at the Hygeia Hospital, Athens from 2010 until 2021 with a mean follow-up time of at least 3 years. Patients were included if after complete diagnostic workup there was no evidence of a nasal or paranasal sinus primary lesion and extension of the ACC. All patients were treated with a combination of endoscopic surgeries performed by the senior author followed by radiotherapy (RT) and/or chemotherapy.Results Three unique illustrative cases (ACC involving the clivus, cavernous sinus and pterygopalatine fossa, one orbital ACC with pterygopalatine fossa and cavernous sinus involvement and one involving cavernous sinus, and Meckel's cave with extension to the foramen rotundum) were identified. All patients underwent subsequently proton or carbon-ion beam radiation therapy.Conclusions Primary intracranial ACCs constitute an extremely rare clinical entity with atypical presentation, challenging diagnostic workup and management. The design of an international web-based database with a detailed report of these tumors would be extremely helpful.
Keywords: adenoid cystic carcinoma; endoscopic transnasal surgery; intracranial ACC; proton beam therapy